THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND ANXIETY LEVELS IN PRE GENERAL ANESTHESIA PATIENTS AT HASTA HUSADA HOSPITAL - Sekar Prana Iswari; rossyana septyasih; Joko Wiyono; swito prastiwi (Jurnal Keperawatan Terapan, 2022)
Surgery is one of the treatment actions that can trigger anxiety because of the physical threat from both surgical procedures and anesthesia. Anxiety responses can have a negative impact on patients if not treated properly. Therefore, psychological support is needed in dealing with anxiety, one of which can be obtained from the family. The purpose of this study was to determine the relationship between family support and anxiety levels in pre general anesthesia patients at Hasta Husada Hospital. The method in this study uses a quantitative research type with a cross-sectional approach. Sampling in this study using purposive sampling technique with a sample size of 30 people. Data processing was carried out statistically using the Spearman Rank correlation test. The results of this study are that most of the respondents received good family support, a total of 16 respondents (53.3 percent) and half of the respondents with a total of 15 respondents (50 percent) experiencing moderate anxiety. The results of the data analysis showed a significance value of (0.001) with a correlation coefficient of (0.592). The conclusion that can be drawn is that there is a relationship between family support and anxiety levels in pre general anesthesia patients at Hasta Husada Hospital. Suggestions from this study are families should be able to increase family support for pre general anesthesia patients to overcome anxiety